ROLE OF INDUSTRY ACADEMIA INTERFACE IN SKILL DEVELOPMENT internalising. - Chatterjee, Nilendu; Biswas, Suchandra; Chattopadhyay, Kalyan ([S.l.] : ROUTLEDGE, 2025)
The book deals with the intricate challenges academia faces in integrating skill development into the curriculum and how improving the industry-academia interface could be a solution through education policies. It responds to the need for skill-centric development, aligning with the demands of Education 4.0 in todays Industry 4.0. This multi-disciplinary volume covers the need for effective collaboration between education sectors and industries, covering the modern-day needs of the labour market and initiatives of the public sector. On the other hand, it emphasises the role of education policies, non-formal education andtraining for teachers in developing skills for different stakeholders of education sectors. The book also highlights how modern-day initiatives like ed-tech start-ups have been redefining skill development and education in the post-COVID period. This book would be useful to the students, researchers and teachers working in the fields of Education, Psychology, Development Studies, Social Work, and Sociology. It would also be an invaluable companion to policy makers, professionals from government and non-government organisations working in the education and social development sectors
Keywords: Education, Higher -- Curricula; EDUCATION / Educational Policy & Reform / General; EDUCATION / Leadership; EDUCATION / General